Role of social safety net programmes for ensuring food security and reducing poverty in char area of Jamalpur district in Bangladesh - Badhan, SA; Haque, S; Akteruzzaman, M; Zaman, N; Nahar, K; Yeasmin, F (Progressive Agriculture, 2019)
The study has been conducted to assess the social safety net programmes for ensuring food security and poverty reduction in char area of Jamalpur district, Bangladesh during the period of July-August in 2016. Survey method was used to collect primary data from Madargonj upazila of Jamalpur district. A total of 60 sample households were selected purposively for collecting data where 25 were under old age allowance, 15 were widow allowance and 20 were VGF/VGD card holders. Descriptive and tabular analysis was used to achieve the major objectives of the study. There are many Safety Net Programmes launched in the study area, like old age allowance, widow allowance, VGD/VGF, test relief, food for works and so on. The findings showed that after getting the allowance, the food consumption pattern, health, etc. are improving. Before joining SSNPs, about 77% people were food insecure but now the value is 68% and their calorie intake is 1834 kcal. The food security index became 0.79 and the food insecure household fall short of required calorie intake by 18 percent. It has been found that about 55% respondents are living below the poverty line but the joining to the SSNP, their situation is improving. Finally, it can be said that the SSNPs are much effective and could be a successful poverty alleviation strategy for the Government of Bangladesh. Progressive Agriculture 30 (1): 75-85, 2019